Jami Al-Azhar: Sejarah, Sistem Pendidikan, Dan Kurikulum Pada Masa Dinasti Fatimiyah - Partahian Partahian; Ahmad Muda Harahap; Handi Wijaya Parinduri (Journal of Innovative and Creativity, 2026)
Jāmi‘ Al-Azhar is one of the most monumental legacies of Islamic civilization and remains the oldest continuously operating Islamic higher education institution in the world. This study aims to examine the history of Jāmi‘ Al-Azhar, the development of its educational system, and the dynamics of its curriculum during the Fatimid Dynasty. Using a library research method with a historical approach, this research analyzes various classical and contemporary sources related to the Fatimid period and the institutional development of Al-Azhar. The findings show that Jāmi‘ Al-Azhar was initially established as a mosque that functioned not only as a place of worship but also as a strategic instrument for disseminating the Ismaili Shi‘a doctrine under Fatimid rule. Over time, Al-Azhar underwent a significant transformation into a higher education institution with a structured learning system. Its curriculum integrated religious sciences (religious sciences) such as the Qur’an, hadith, fiqh, and theology with rational and general sciences (secular sciences), including philosophy, medicine, astronomy, mathematics, and logic. Teaching methods such as halaqah and scholarly discussions fostered a strong intellectual tradition. Despite the decline of the Fatimid Dynasty, Al-Azhar survived political changes and continued to play a crucial role in Islamic education. This study concludes that Jāmi‘ Al-Azhar represents a historical proof of the advanced educational foundations of Islam and its ability to adapt to changing times.